Rancang Bangun Sistem Pengelolaan Barang Berbasis Website Menggunakan Metode Prototype (Studi Kasus: Toko Wilda) - Wahyu Hidayatullah; Ade Andri Hendriadi; Apriade Voutama (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Manual inventory management often leads to recording errors, delayed data updates, and difficulties in monitoring stock levels in real time. This issue was identified at Wilda Store, where inventory management processes were still conducted using conventional record-keeping methods. This study aims to design and develop a website-based inventory management system using the Prototype method to improve inventory management effectiveness. The Prototype method was implemented through the stages of initial requirement, design, prototype, user evaluation, review and update, development, and testing. The developed system provides several features, including an analytics dashboard, product and product variant management, inventory monitoring, incoming goods transactions, outgoing goods transactions, return transactions, and price change reports. System testing was conducted using Black Box Testing and White Box Testing. The Black Box Testing results showed that all system features functioned according to the specified requirements, while White Box Testing indicated that all independent paths could be executed according to the designed program logic. The results demonstrate that the developed system improves inventory management by providing a more structured, accurate, and integrated process, thereby supporting operational activities at Wilda Store more effectively.